Mediação da leitura em bibliotecas públicas - Rasteli, Alessandro [UNESP] (2013)
Discusses the mediation of reading in public libraries in contemporary society and the role of mediator librarian reading these cultural facilities. The survey, order exploratory and qualitative, objective analysis of mediation activities developed in public libraries Administrative Region of Marilia, which comprises 51 municipalities, among which the sample we selected for this study. Considering the universe of libraries that develop reading mediation, we question the character of those actions from the point of view of what is distinguished as appropriation of reading, reading promotion and excitement of reading. From these considerations, it was proposed the following objectives: identify monitoring activities of reading in public libraries in order to understand the scope of these institutions within the field of training practices reader, and study skills in information librarian mediator reading in the public library, addressing the social role and their participation in the formation of the readers. Given these considerations, the problem of this research sought to find answers to the following question: how public libraries of Marilia/SP are developing mediation actions of reading, to generate communities of users able to competently integrate the informational universe and sociocultural ? These reflections express cogitations in several activities focused on the reader, as standalone or in training, but also in combining the theory of reading the referrals of pedagogical practice, seeking to understand how this action in everyday public libraries, and work done by the librarian